How Robots Change Within-Firm Wage Inequality - Erling Barth; Marianne Roed; Pal Schone; Janis Umblijs (Institute of Labor Economics (IZA), 2020)
Using novel matched employer-employee register data with firm-level information on the introduction of industrial robots, this paper analysis the impact of robots on the wages of workers in the manufacturing sector. The results show that industrial robots increase wages for high-skilled workers relative to low-skilled workers, hence robots increases the skill-premium within firms. Furthermore, we find that employees in managerial positions benefit more from robotisation than those in STEM or professional occupations. Overall, our results suggest that the introduction of industrial robots has a positive effect on the average wages of manufacturing workers in Norway.
Keywords: J01; J08; O33; E24; 330; automation; robotisation; labour economics; wages; technological change